Zrównoważona karta wyników dla szpitala - Nieplowicz, Maria (Balanced Scorecard for Hospital, 2007)
The article presents the concept of the Balanced Scorecard and the Balanced Scorecard for hospital. The summary indicates the advantages of using the Balanced Scorecard.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 395-400